Cuantificación y caracterización de agua y efluentes en establecimientos lecheros II. Calidad de efluentes y eficiencia de los procesos de tratamiento - Nosetti, L. (2002)
This study was carried out in three dairy production areas in Buenos Aires. Effluent quality, treatment process efficiency, water management strategies and environmental contamination risk by effluent discharge, was characterized in 9 dairy farms. Holding area feces were measured. Treatment lagoons were sampled. Physicochemical and microbiological qualities, and BOD and COD were determined, and used as environmental risk indicators. Plate-cooler water management strategies were established in order to divide the dairy farms in two groups (G1 and G2). Treatment lagoons were inefficient in regards to effluent treatment. BOD, COD, nitrogen (N), phosphorus (P) and enterococci found in the samples were not within acceptable values according to effluent discharge guidelines. NPK concentration would allow its potential use as a nutrient source. Variability found in the several parameters measured is related to the different lagoons? characteristics and water management strategies. Significant differences (p<0.05) were detected in N and P contents between G1 and G2. Proper environmental management in animal production systems requires an appropriate wastewater handling within each farm.